2007
DOI: 10.1542/peds.2006-2407
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes and Participation in Young Adulthood for Very Preterm and Very Low Birth Weight Infants: The Dutch Project on Preterm and Small for Gestational Age Infants at 19 Years of Age

Abstract: A total of 12.6% of young adults who were born very preterm and/or with a very low birth weight had moderate or severe problems in cognitive or neurosensory functioning. Compared with the general Dutch population, twice as many young adults who were born very preterm and/or with a very low birth weight were poorly educated, and 3 times as many were neither employed nor in school at age 19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
1
11

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(122 citation statements)
references
References 40 publications
3
107
1
11
Order By: Relevance
“…[41][42][43][44] The study that is most similar to ours is the Netherlands Project on Preterm and Small for Gestational Age Infants study in VLBW/VP infants born in 1983. 45,46 As in our study, Hille et al, 46 reporting from the POPS study cohort at age 19 years, found that VLBW survivors had greater difficulty establishing social contacts but did not have elevated risks of psychopathology compared with their term-born peers.…”
Section: Discussionsupporting
confidence: 67%
“…[41][42][43][44] The study that is most similar to ours is the Netherlands Project on Preterm and Small for Gestational Age Infants study in VLBW/VP infants born in 1983. 45,46 As in our study, Hille et al, 46 reporting from the POPS study cohort at age 19 years, found that VLBW survivors had greater difficulty establishing social contacts but did not have elevated risks of psychopathology compared with their term-born peers.…”
Section: Discussionsupporting
confidence: 67%
“…[1][2][3][4]6,42 In the general population, low childhood IQ has been found to predict low adult SES, 43,44 as well as reduced survival and health into old age. 45,46 IQ is thus an important marker of brain health.…”
Section: Figurementioning
confidence: 99%
“…The incidence of preterm birth has increased significantly in the past decades, but is associated with higher survival rates 1 and a lower incidence of major disabilities than in the past. 2 However, there is strong evidence that preterm survivors without brain malformations, congenital infection, or metabolic disease and with normal outcomes or mild abnormalities on structural brain magnetic resonance imaging (MRI) may experience more problems of motor, cognitive, language, and behavioural functioning throughout childhood and young adulthood. [3][4][5][6] These sequelae have been attributed to perinatal brain injuries, 7,8 which frequently involve white matter, 9 during normal brain maturation.…”
Section: Interpretation Significant Changes In Fractional Anisotropy mentioning
confidence: 99%